2009
DOI: 10.1007/12_2009_13
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Transitions and Instabilities in Surfactant Wormlike Micelles

Abstract: In this review, we report recent developments on the shear-induced transitions and instabilities found in surfactant wormlike micelles. The survey focuses on the nonlinear shear rheology and covers a broad range of surfactant concentrations, from the dilute to the liquid-crystalline states and including the semidilute and concentrated regimes. Based on a systematic analysis of many surfactant systems, the present approach aims to identify the essential features of the transitions. It is suggested that these fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
155
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(172 citation statements)
references
References 321 publications
(908 reference statements)
13
155
1
3
Order By: Relevance
“…The complex viscosity modulus was adjusted using ( ) = 1 + , where = denotes the static viscosity. At T = 27 °C, the viscoelastic parameters are = 7.1 ± 0.1 Pa, = 0.14 ± 0.01 s and = 1.0 ± 0.1 Pa s. These results confirm those published for the first time on the same system two decades ago [39,40,42].…”
Section: -Micro-rheology Of Wormlike Micellessupporting
confidence: 88%
“…The complex viscosity modulus was adjusted using ( ) = 1 + , where = denotes the static viscosity. At T = 27 °C, the viscoelastic parameters are = 7.1 ± 0.1 Pa, = 0.14 ± 0.01 s and = 1.0 ± 0.1 Pa s. These results confirm those published for the first time on the same system two decades ago [39,40,42].…”
Section: -Micro-rheology Of Wormlike Micellessupporting
confidence: 88%
“…The relaxation time of the SIS was found to range from several seconds to a couple of hours (26). Similarly, others observed birefringent SIS formation in a solution of surfactant and salt under shear and subsequent disappearance of the birefringent structures after the flow was stopped (24,37). Based on time-dependent SALS studies under a simple shear flow, Kadoma and van Egmond (12) suggested that CTAB/NaSal-based (0.03/ 0.24 M) SISs consist of highly elongated and locally concentrated micellar strings.…”
Section: Flow-induced Structuresmentioning
confidence: 62%
“…Based on time-dependent SALS studies under a simple shear flow, Kadoma and van Egmond (12) suggested that CTAB/NaSal-based (0.03/ 0.24 M) SISs consist of highly elongated and locally concentrated micellar strings. The SIS has since been widely studied using birefringence, light scattering, neutron scattering, X-ray scattering, and NMR (21,24).…”
Section: Flow-induced Structuresmentioning
confidence: 99%
“…This scenario has been confirmed experimentally with various techniques like pure viscom-etry, velocimetry, birefringence, etc. (see [13] and Ref. therein) and we shall highlight typical observations in the first section of the present paper.…”
Section: Introductionmentioning
confidence: 66%